Impact of Brand Credibility on Attitude Toward Brand and Brand Loyalty among Samsung Smartphone Users in Samarinda - Selvi Intan Nabila; Doddy Adhimursandi (Economics and Digital Business Review, 2026)
The escalating competition within the smartphone sector has rendered it increasingly arduous for brands to uphold customer allegiance, particularly in developing markets such as Indonesia. This investigation endeavors to analyze the influence of brand credibility on consumer attitudes toward brands and brand loyalty among Samsung smartphone users in Samarinda. This research adopts a quantitative methodology, utilizing survey data gathered from 120 participants and scrutinized via Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings indicate that brand credibility exerts a positive and significant influence on consumer attitudes toward brands, and consumer attitudes toward brands positively and significantly affect brand loyalty. Nevertheless, brand credibility does not demonstrate a significant direct impact on brand loyalty. These results underscore the necessity of cultivating affirmative consumer attitudes to bolster customer loyalty within a competitive marketplace.